Risk Factors for Bile Aspiration and its Impact on Clinical Outcomes. Issue 12 (7th December 2021) - Rosen, Rachel; Lurie, Margot; Kane, Madeline; DiFilippo, Courtney; Cohen, Alexandra; Freiberger, Dawn; Boyer, Debra; Visner, Gary; Narvaez-Rivas, Monica; Liu, Enju; Setchell, Kenneth
Abstract : INTRODUCTION: Bile reflux may cause for lung allograft rejection, yet there are no studies that determine (i) the relationship between gastric and lung bile concentrations, (ii) whether bile is present in lungs of nontransplant patients, (iii) the relationship between gastric dysmotility and lung bile, (iv) the impact of reflux therapies on lung bile, and (v) whether lung bile worsens outcomes in nontransplant patients. This study will address these gaps in the literature. METHODS: We prospectively recruited lung transplant (LTX) patients and nontransplant patients with respiratory symptoms (RP) and collected paired gastric and lung samples. Bile concentration and composition of samples was assessed using liquid chromatography–mass spectrometry. Bile results were compared with clinical parameters, including the presence of esophagitis, gastric dysmotility, and/or pathologic gastroesophageal reflux. RESULTS: Seventy patients (48 RP and 22 LTX) were recruited. Overall, 100% of gastric and 98% of bronchoalveolar lavage samples contained bile. The mean gastric bile concentrations in RP and LTX patients were 280 ± 703 nmol/L and 1, 004 ± 1721 nmol/L, respectively ( P = 0.02). There was no difference in lung bile concentrations between RP (9 ± 30 nmol/L) and LTX (11 ± 15 nmol/L, P = 0.7). Patients with delayed gastric emptying had higher lung bile concentrations (15.5 ± 18.8 nmol/L) than patients with normal gastric emptying (4.8 ± 5.7 nmol/L, P = 0.05) independently of reflux burden. Proton pump inhibitor use increased the proportion of unconjugated gastric bile acids. High lung bile concentrations were associated with an increased risk of hospitalization and longer hospital stays in RP patients ( P < 0.05). DISCUSSION: Lung bile is almost universally present in symptomatic patients, and higher concentrations are associated with poorer respiratory outcomes.